2020
DOI: 10.1371/journal.pone.0242798
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression and purification of recombinant dermatopontin in Escherichia coli

Abstract: Dermatopontin (DPT) is an extracellular matrix (ECM) protein with diversified pharmaceutical applications. It plays important role in cell adhesion/migration, angiogenesis and ECM maintenance. The recombinant production of this protein will enable further exploration of its multifaceted functions. In this study, DPT protein has been expressed in Escherichia coli (E.coli) aiming at cost effective recombinant production. The E.coli GJ1158 expression system was transformed with constructed recombinant vector (pRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…The endothelial cell migration and angiogenic potential of this purified fusion protein was comparable to the VEGF, a crucial inducer of angiogenesis. Similar observations of neovascularization were reported, induced by E. coli- derived recombinant asparaginyl-tRNA synthetase 35 and dermatopontin 36 proteins. It is reported that HAND2 regulates angiogenesis through the Notch signaling pathway 59 .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The endothelial cell migration and angiogenic potential of this purified fusion protein was comparable to the VEGF, a crucial inducer of angiogenesis. Similar observations of neovascularization were reported, induced by E. coli- derived recombinant asparaginyl-tRNA synthetase 35 and dermatopontin 36 proteins. It is reported that HAND2 regulates angiogenesis through the Notch signaling pathway 59 .…”
Section: Discussionsupporting
confidence: 86%
“…In order to study the angiogenic potential of HAND2 protein, we performed a chicken CAM assay. The chick embryo model is a widely used ex vivo model to study the angiogenic/anti-angiogenic potential of various biological molecules including recombinant proteins 35 , 36 . For the slow diffusion of recombinant protein, we soaked the filter paper discs in the protein solution and gently placed them on the CAMs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations